Effect of Iron (Fe) heavy metal content at different pH on the germination of seven soybean varieties in Indonesia - Timotiwu, Paul Benyamin; Agustiansyah, Agustiansyah; Muslimah, Dini (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Greater use of acid soil has expanded the area under cultivation for soybeans; however, acid soil is associated with heavy mineral toxicity, including Iron (Fe). This investigation looked at how well soybean seeds germinated in media containing heavy metal Fe and how the pH of the media affected the viability of soybean seeds. This research was conducted at the Seed and Plant Breeding Laboratory at the University of Lampung, Indonesia. The experimental design was a randomized block design. The first factor was seven soybean local varieties – Grobogan, Anjasmoro, Derap 1, Detap 1, Dena 1, Deja 1, and Dega 1 – and the second factor was heavy metal Fe solution pH of 6–7 and 4.5 and without heavy metal Fe (control). Seed viability in heavy metal Fe medium was assessed using radicle emergence, germination capacity or percentage, germination speed, number of normal seedlings, normal seedling hypocotyl length, main root length of regular seedlings, and normal shoot dry weight. This research found that heavy metal Fe affected soybeans’ seeds’ viability in pH 6–7 and 4.5. The observed data showed that all seeds’ viability variables in media with heavy metal Fe, both in pH 6–7 and in pH 4.5, differ from the control media. The seed viability in media heavy metal Fe pH 6–7 was not significantly different from the control media, but in pH 4.5, the difference is significant. Soybean varieties’ characteristics also influence how heavy metal Fe in different pH affects seed viability. Overall, Anjasmoro, Deja, Grobogan, and Dega were the types that consistently demonstrated resistance or adaptation to heavy metal Fe existence, while Dena, Derap, and Detap are susceptible to heavy metal Fe existence. Seed viability in Iron medium is not always related to seed physical performance; therefore, before planting soybean in acid soil, it is recommended to conduct a seed viability test.